Upaya Meningkatkan Kemampuan Berbahasa pada Anak Usia Dini melalui Pemanfaatan Permainan Edukatif Boneka Jari - Widasih, Jarti; Suprayitno, Kabul (ARZUSIN, 2025)
Language skills are a crucial aspect of early childhood development, serving as a foundation for cognitive processes, social interactions, and future learning experiences. Despite this significance, many young children continue to exhibit delays in both speaking and comprehension. This study aims to explore the use of finger puppet educational games to enhance the language skills of early childhood students at TK Tunas Putra in Desa Mantren, assess improvements in their language abilities, and identify factors that support or inhibit implementation. Employing a classroom action research (CAR) approach, the study was conducted over two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observations, interviews, and documentation, and were analyzed using descriptive qualitative methods. The findings indicate that finger puppet games significantly improved children's language skills, evidenced by enhanced speaking abilities, enriched vocabulary, and increased confidence in peer communication. The study concludes that finger puppet educational games are an effective medium for fostering language development in young children. Furthermore, this research underscores the importance of teacher creativity in selecting appropriate learning media that align with children's characteristics, thereby optimizing their overall development, particularly in the language domain.